Geochemical Signature of Magmatic-Hydrothermal Fluids Exsolved from the Beauvoir Rare-Metal Granite (Massif Central, France): Insights from LA-ICPMS Analysis of Primary Fluid Inclusions - Matthieu Harlaux; Julien Mercadier; Wilédio Marc-Emile Bonzi; Valentin Kremer; Christian Marignac; Michel Cuney (Geofluids)
The Beauvoir granite (Massif Central, France) represents an exceptional case in the European Variscan belt of a peraluminous rare-metal granite crosscutting an early W stockwork. The latter was strongly overprinted by rare-metal magmatic-hydrothermal fluids derived from the Beauvoir granite, resulting in a massive topazification of the quartz-ferberite vein system. This work presents a complete study of primary fluid inclusions hosted in quartz and topaz from the Beauvoir granite and the metasomatized stockwork, in order to characterize the geochemical composition of the magmatic fluids exsolved during the crystallization of this evolved rare-metal peraluminous granite. Microthermometric and Raman spectrometry data show that the earliest fluid (L1) is of high temperature (500 to >600°C), high salinity (17–28 wt.% NaCl eq), and Li-rich (Te<−70°C) with Na/Li ratios ~5. LA-ICPMS analyses of L1-type fluid inclusions reveal that the chemical composition of this magmatic-hydrothermal fluid is dominated by Na, K, Cs, and Rb, with significant concentrations (101–104 ppm) in rare-metals (W, Nb, Ta, Sn, and Li). This study demonstrates that primary fluid inclusions preserved the pristine signature of the magmatic-hydrothermal fluids in the Beauvoir granite but also in the metasomatized W stockwork, despite the distance from the granitic cupola (>100 m) and interaction with external fluids.